First results of the activity of advisory and treatment-and-diagnostic center of Siberian State Medical University clinics - V. M. Shevelyov; Yu. R. Khasanshin; Ye. V. Khasanshina (Бюллетень сибирской медицины)
It has been described a variant of practical use of resource-saving technologies in health care service system on the level of medical university. This is a setting into operation of advisory and treatment — and-diagnostic center (ATDC) of SibSMU clinics. The main point of clinic activity as a treatment-and-preventive establishment under the medical university has been discovered and the need of resource saving has been grounded. Mechanism of resource saving by redistribution of patient stream over the stages of medical care with the succession reservation in medical service along with the active use of modern information technologies. Organizational aspects of the center formation and its profile have been cleared. Base components of the used information and communication technologies during the organization of the center informational system have been indicated. The positive dynamics of activity factors resulted from the setting into operation of SibSMU clinic ATDC has been shown as well as the following effective and qualitative growth of medical service in SibSMU clinics.